2012
DOI: 10.1111/j.1748-5827.2012.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of cochlear hearing status in dogs using evoked otoacoustic emissions

Abstract: Transient-evoked otoacoustic emission and distortion-product otoacoustic emission testing provided a rapid, non-invasive frequency-specific assessment of cochlear function. Transient-evoked otoacoustic emission and distortion product otoacoustic emission testing is suitable as a screening procedure to detect loss of cochlear function in dogs, although further investigation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Constant noise can have physiologic and psychological effects in several nonhuman species [2]. This investigation was focused specifically on the deleterious effects of environmental noise on the auditory system in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constant noise can have physiologic and psychological effects in several nonhuman species [2]. This investigation was focused specifically on the deleterious effects of environmental noise on the auditory system in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Although, anatomically, the canine ear canal differs from humans and the canine cochlea differs anatomically (where dogs have a higher range of frequencies of hearing than humans), functional magnetic resonance imaging (fMRI) studies have shown analogies between human and canine auditory cortices and central auditory systems [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%